Structural exploration of viral matrix protein 40 interaction with the transition metal ions (Ag+ and Cu2+). Issue 11 (24th July 2019) - Saranya, V.; Shankar, R.; Vijayakumar, S.
Abstract: Here, a theoretical and comprehensive study of the structural features and interaction properties of viral protein 40 is being briefed out to understand the mechanism of Ebola virus (EV) with structural and orbital analysis. In general, viral protein 40 is the key protein for the oligomerization, the N-terminal loop region in the viral protein 40 and it is essential for the viral replication in Ebola. The electronic structures of native N-terminal loop (His124-Asn134) and metalized (M n+ =Ag + and Cu 2+ ) complexes are optimized at the M06-2X/LANL2DZ level of theory. Among M n+ -interacted N-loop complexes, Cu 2+ -interacted N-terminal loop complex has the highest interaction energy of –973.519 kcal/mol and also it has the stabilization energy in the range of 9.92 kcal/mol. The cation-π interactions between His124, Pro131 and Arg134 residues are the important factor, which enhances the interaction energy of viral protein 40. Due to the chelation behavior of metal ions, the backbone and the side chains of N-terminal loop regions are deviated from the planarity that results in the formation of classical hydrogen bonds between N-terminal loop regions. Molecular dynamics simulation studies also revealed that the structural transformations of Nloop into a stable α-helix and β-sheet folded conformations due to the interaction of Ag + and Cu 2+ ions in the N-terminal loop region. The hydrogen bond formation and hydrophobic interactions are responsible for the stability and structural changes in N-terminal loop region. Therefore, it is clear that interaction of metal ion with viral protein-40 reduces the replication of the disease by inducing the secondary structural changes. Communicated by Ramaswamy H. Sarma